Response of semi-rigid steel frames to sequential earthquakes - Hassan, Emad M.; Admuthe, Sushant; Mahmoud, Hussam (Journal of constructional steel research, 2020)
In a seismic event, large number of aftershocks are generally triggered due to the complex interaction within and between tectonic plates. Even though aftershocks are typically smaller in magnitude than mainshocks, their ground-motion intensity, measured by peak ground acceleration, is not always smaller. Moreover, mainshocks can result in permanent damage to structural components. As a result, the vulnerability of structures to extensive damage and complete collapse due to aftershocks could increase. Despite their importance in evaluating the true risk of system failure and collapse, the inclusion of aftershocks in code provisions and guidelines for seismic risk assessment and performance-based engineering is lacking. In this study, three semi-rigid frames, with connection capacities of 50%, 60%, and 70% of the plastic moment of the beam, were designed and their performance under mainshock-aftershock sequences assessed. The objective of this study, pertaining to the seismic performance of the frames, is twofold. First, is to develop fragility functions for the subject frames under sequential mainshock-aftershock events. Second, is to evaluate the extent of spread of inelasticity and period elongation in the investigated frames as a result of the sequential events. A new method for selection and scaling of mainshock-aftershock sequences is proposed and non-linear time history analysis of the frames is conducted. The results show that the inclusion of the aftershocks increases the probability of reaching or exceeding a particular damage limit state in the frames, primarily due to the considerable period elongation resulting from the induced permanent damages. [Display omitted] •We designed and developed numerical models of three semi-rigid steel frames.•We included various inelastic features of the connections when developing the models.•We developed a new approach for selecting and scaling sequential mainshock-aftershock ground motions.•We subjected the frames to the ground motions and developed new fragility functions.•We evaluated the performance of the frames to assess their period elongation under the seismic demand.